AN ANALYSIS OF WOMEN DISCRIMINATION IN LYNN NOTTAGE’S RUINED - SITI MARYAM; IKA TRISNANTASARI (AESTHETICS : Jurnal Fakultas Sastra Universitas Gresik, 2019)
Women discrimination in the theory of gender discrimination is the difference in the treatment of women, violations of their rights, and women as victims who endanger or limit access to opportunities available to other members of the community.  The portrayal of female discrimination can be found in the drama entitled Ruined. This drama tells of the war in the Congo which led to raping and sexual violence which had been applied as a powerful weapon in achieving military and economic goals.  The main target is women.  Researchers wants to find out how women's discrimination occurs, then what are the factors and what are the effects of female discrimination. The purpose of this research is to find out how women discrimination occurs in Congo, find out the causes of discrimination and the impact of discrimination on the four female characters in the dramaThis research was designed in a qualitative manner using an explanatory method. The research data shows that there are four female characters who experience discrimination.  They are Mama Nadi, Josephine, Sophie, and Salima.  Discrimination factors found in drama such as economic ambition, social masculinity, and impunity. Furthermore, the results of the study showed that female discrimination had a major impact on the four characteristics of women victims and had physical and social impacts, such as stress, mental disorders, trauma, venereal disease, and even the greatest impact was suicide.Keyword: Women Discrimination